2017
DOI: 10.1016/j.enbuild.2017.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of predictive control in a commercial building energy management system using neural networks

Abstract: Most existing commercial building energy management systems (BEMS) are reactive rule-based. This means that an action is produced when an event occurs. In consequence, these systems cannot predict future scenarios and anticipate events to optimize building operation. This paper presents the procedure of implementing a predictive control strategy in a commercial BEMS for boilers in buildings, and describes the results achieved. The proposed control is based on a neural network that turns on the boiler each day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…Several research streams recently dealt with the efficient operation of equipment and energy resources in smart buildings, by investigating different fields. Examples are the optimization of HVAC systems based on Model Predictive Control (MPC) algorithms or Neural Networks (NNs) [14][15][16][17], or the application of flexible control strategies, Demand Side Management (DSM) actions, and Demand Response (DR) programs [2,[18][19][20]. The application of such control strategies is implemented in single family houses through the so-called Home Energy Management Systems (HEMSs), such as well as in large buildings, by means of Building Energy Management Systems (BEMSs).…”
Section: Distributed Management Of Energy Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research streams recently dealt with the efficient operation of equipment and energy resources in smart buildings, by investigating different fields. Examples are the optimization of HVAC systems based on Model Predictive Control (MPC) algorithms or Neural Networks (NNs) [14][15][16][17], or the application of flexible control strategies, Demand Side Management (DSM) actions, and Demand Response (DR) programs [2,[18][19][20]. The application of such control strategies is implemented in single family houses through the so-called Home Energy Management Systems (HEMSs), such as well as in large buildings, by means of Building Energy Management Systems (BEMSs).…”
Section: Distributed Management Of Energy Resourcesmentioning
confidence: 99%
“…In the latter case, advanced control functions are usually defined by supervisory levels and then communicated to local controllers and actuators by means of local networks. Conversely, the implementation of DSM actions and DR programs, which involves the participation of third-party agents, such as Distribution System Operators (DSOs) or independent aggregators, requires the use of WANs [7,17].…”
Section: Distributed Management Of Energy Resourcesmentioning
confidence: 99%
“…An equivalent method has been employed for setback moment determination of cooling system in other existing studies . Similarly, Macarulla et al tested a control strategy to determine the optimum starting time of an office building boiler to achieve thermal comfort at the beginning of each working day. They managed to save 20% of energy while guaranteeing thermal comfort.…”
Section: Neural Network Applications Over a Building's Lifementioning
confidence: 99%
“…According to the study, the energy saving potential of a building to be 7.4 MWh/year. Macarulla et al [6] present the procedure of implementing a predictive control strategy in a commercial BEMS for boilers in buildings based on a neural network that turned on the boiler each day at the optimum time, according to the surrounding environment, to achieve thermal comfort levels at the beginning of the working day. The results showed that the implementation of predictive control in a BEMS for building boilers could reduce the energy required to heat the building by around 20% without compromising the user's comfort.…”
Section: Literature Reviewmentioning
confidence: 99%